ANALISIS STRATEGI PROMOSI DALAM PASAR LUAR NEGERI GUNA MENINGKATKAN PRODUK PERUSAHAAN ( STUDI KASUS : PT. KALBE FARMA Tbk ) - Anggita Rizkia; Ahmad Muharmansyah; Anastasya Br Ginting; Elsa Mayori; Indah Aryani; Suhairi Suhairi (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
Thus the purpose of this study is to analyze the marketing promotion strategy implemented by PT Kalbe Farma Tbk's Marketing Area to build competitiveness and improve the pharmaceutical industry, especially in selling generic drugs. Business strategy is a tool that gives a company a competitive advantage. Competitive advantage is a prerequisite for companies to maintain the desired competitive advantage in order to remain profitable and sustainable. consumer purchases continue to increase, advertising and other promotional tools must be balanced by giving discounts and gifts that increase sales value. The research method used is a qualitative approach research method. Qualitative methodology is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. Data collection techniques are carried out by analyzing literature related to research, scientific journals, books, magazines and others. He admitted that 400 of Kalbe's products were also copies of generic foreign products. Through Innogene, Kalbe will be listed as the first local pharmaceutical company to launch various innovative and original products made by Kalbe. The results show that from the analysis of external factors, the opportunities for foreign market distributor promotion strategies for Kalbe are: good pharmaceutical market growth, product innovation and patents, pharmaceutical regulatory policies that benefit incumbent players, information technology capabilities, product technology capabilities and processes, capabilities of economies of scale, broad product lines, ability to build quality. and supply chain capabilities.